Territorial conditioning and intertwined stories in Latin America - Costa, Everaldo Batista da (2020)
In the context of the Latin American continent, the Mexican and Brazilian colonial experience (like all others) contain singularities that deserve to be emphasized. In a recent study, it was possible to recognize, once again, the dramatic plot of different forms of social existence in Latin America. The development of the project “Baroque conditioning of the New Spanish territory and Latin American original decoloniality: convents, prisons and Indian villages”, together with the IGG-UNAM, made it possible to understand how our territories and bodies were and continue to be conditioned and violated (with their people) under the cover of the discourse of freedom (yesterday) and democracy (today). The approach can be found in this new issue of PatryTer, which presents articles concerned with the socio-spatial destiny of our continent and the cultural values ​​of its people, when it is going through one of the greatest crises in its history: from a deep political crisis to a miserable crisis of ideologies, at the core of a continuum of crises proper to European modernity from Latin America. This journal has focused on that concern (Mariano, 2020; Valverde, 2020; Alvarado, 2019; Ferreira & Araújo Sobrinho, 2019; Souza, 2019; Cabrales, 2018; Lemos, 2018, Alves, 2018, etc.).